Research Methods in Teacher Education: Meaningful Engagement Through Service-Learning - Froehlich, Dominik E.; Hobusch, Ulrich; Moeslinger, Karoline (Frontiers in Education, 2021)
Competence in research methods is a major contribution to (future) teachers’ professionalism. In the pedagogical approach presented here, which we call the Teaching Clinic, we combine service-learning and design-based research to create meaningful learning engagements. We present two cases to illustrate the objectives, processes, and outcomes of the service-learning projects and reflect about both in terms of learning and service outcomes. This includes discussions of how this pedagogical approach led to motivation and engagement, how principles of transfer of training are obeyed, and what this means quite generally for school-university relationships.